Giant gastric schwannoma presenting with upper gastrointestinal bleeding - Hakan ŞENTÜRK,; Abdullah SONSUZ,; Cihan URA MD,; Süha GÖKSAL MD,; Sebati ÖZDEMİR,; Ahsev BALIC MD,; Perihan AKIN, (Turkish Journal of Gastroenterology, 2019)
-